Search for W H associated production in 5.3 fb(-1) of p(p)over-bar collisions at the Fermilab Tevatron - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Demina, R.; et al. (Elsevier B.V., 2011)
We present a search for associated production of Higgs and W bosons in p (p) over bar collisions at a center of mass energy of root s = 1.96 TeV in 5.3 fb(-1) of integrated luminosity recorded by the do experiment. Multivariate analysis techniques are applied to events containing one lepton, an imbalance in transverse energy, and one or two b-tagged jets to discriminate a potential WH signal from Standard Model backgrounds. We observe good agreement between data and expected backgrounds, and set an upper limit of 4.5 (at 95% confidence level and for m(H) = 115 GeV) on the ratio of the WH cross section multiplied by the branching fraction of H -> b (b) over bar to its Standard Model prediction, which is consistent with an expected limit of 4.8. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Tevatron; Standard Model; Higgs boson; Electroweak symmetry breaking